The roles of exosomal immune checkpoint proteins in tumors - Cheng Xing (BMC, 2021)
Abstract Targeting immune checkpoints has achieved great therapeutic effects in the treatment of early-stage tumors. However, most patients develop adaptive resistance to this therapy. The latest evidence demonstrates that tumor-derived exosomes may play a key role in systemic immune suppression and tumor progression. In this article, we highlight the role of exosomal immune checkpoint proteins in tumor immunity, with an emphasis on programmed death ligand 1 (PD-L1) and cytotoxic T lymphocyte-associated antigen 4 (CTLA-4), as well as emerging evidence on roles of T cell immunoglobulin-3 (TIM-3), arginase 1 (ARG1), and estrogen receptor binding fragment-associated antigen 9 (EBAG9) expressed by exosomes.